Challenges of clinical translation from single‐cell sequencing to measures in clinical biochemistry of haematology: Definition of immune cell identities - Xuanqi Liu; Xiangdong Wang; Charles A. Powell; Diane C. Wang (Wiley, 2023)
Abstract Peripheral immune cells play important roles in the maintenance of systemic and microenvironmental hemostasis. Measurements of circulating blood cells by single‐cell RNA sequencing (scRNA‐seq) were proposed as one of the routine measures in the clinical biochemistry of haematology. Out of translational challenges, defining precise identities of cell subsets and states is more difficult, due to the complexity of immune cell development, location, regulation, function, and metabolism. It is also a challenge to precisely interpret the clinical significance and impact of each cell identity marker gene panel (ciMGPs). ciMGPs have the potential to advance the understanding of systemic responses to the disease, identify disease‐specific biomarkers and define cell heterogeneity. Recently, a large number of peripheral cell subsets and expanding/activating states have been identified and validated for use in the fast developments in clinical single‐cell biomedicine. Defining the specificity, measurability and repeatability of cell subsets/states is important for the translation of peripheral scRNA‐seq in clinical haematology and biochemistry. The development of standard operating procedures and the performance of clinical trials in large populations of various ages, diseases, and therapies will promote the clinical translation of ciMGPs to measures. Thus, defining cell subset/state identities will provide the multi‐dimensional and comprehensive readouts of systemic immune cells, the precision monitoring of immune dynamics, and a deeper understanding of the disease and response to therapy.